Online fashion consumerism among women: The interplay of digital experiences and decision-making – a mediated moderated analysis - Madhura K.; Niyaz Panakaje; S. M. Riha Parvin; Shakira Irfana; Mural Henrita Cutinha; Yatheen A; Rovina Sharon Soans (Innovative Marketing)
This research examines how digital experiences on social media influence women’s buying behavior towards online fashion. Furthermore, it examines how challenges moderate these purchase decisions, and how attitudes mediate these purchase decisions. The research executed in Southern Karnataka state of India obtained the responses from 800 women employed through a formal questionnaire and a systematic method of selection. The measurement models and structural models were examined using AMOS 23. The study indicates that when women engage with social media and gain easy access to information and feedback through reviews, they develop a stronger positive outlook on buying fashion. These favourable opinions lead directly to consumer buying choices and additionally shape the relationship between the digital experience and their purchasing patterns on online sites. The issues regarding online shopping discourage the transformation of positive views into real transactions. The results reveal that ease of use, exemplified by intuitive navigation (β = 0.188) and easy access to product information, positively affect consumer attitudes. Electronic word-of-mouth (E-WOM), including reviews and recommendations (β = 0.456), also significantly boosts trust, leading to higher purchase intentions. Attitude acts as a strong mediator, with its effect on buying behavior showing a β coefficient of 0.609. However, challenges like concerns over data privacy and difficulties in verifying review authenticity negatively affect the attitude-behavior relationship, with a moderating effect of β = -0.092. The findings show the necessity for more robust data protection laws and better accessibility of online reviews to minimize seen threats and enhance shopper trust in digital clothing shopping.